Peranan Kepemimpinan Satuan Polisi Pamong Praja Provinsi Sumatera Utara Dalam Peningkatan Pelayanan Terhadap Masyarakat - Albert Harianja; Humaizi; Heri Kusmanto (PERSPEKTIF, 2023)
The purpose of this study, among other things, is to identify and analyze the role of leadership and the supporting and inhibiting factors faced by the Civil Service Police Unit of North Sumatra Province in improving services to the community. The research design used in this study is a descriptive method with a qualitative approach. The data were obtained directly from the field and the data analysis technique used in this study was to use the steps proposed by Bungin (Ed) (2003), which are as follows: Data Collection. Data Reduction (Data Reduction). Display Data. And Verification and Confirmation of Conclusions (Conclusion Drawing and Verification) The results of the study concluded that the role of leadership in the civil service police unit of North Sumatra Province in improving service to the community is seen in its role as a determinant of direction, as a spearhead of change and as a spokesperson. Supporting factors encountered are the relationship between superiors and subordinates, task structure and position strength in Satpol PP of North Sumatra Province. The inhibiting factors encountered include work initiatives, facilities and infrastructure and budget.